Perflubron Distribution During Transition From Gas to Total Liquid Ventilation - Sage, Michaël; Stowe, Symon; Adler, Andy; Forand-Choinière, Claudia; Nadeau, Mathieu; Berger, Claire; Marouan, Sofia; Micheau, Philippe; Tissier, Renaud; Praud, Jean-Paul; Fortin-Pellerin, Étienne (Frontiers in Physiology, 2018)
Total liquid ventilation (TLV) using perfluorocarbons has shown promising results for the management of neonatal respiratory distress. However, one important safety consideration for TLV is a better understanding of the early events during the transition to TLV, especially regarding the fate of residual air in the non-dependent-lung regions. Our objective was to assess perflubron distribution during transition to TLV using electrical impedance tomography, complemented by fluoroscopy, in a neonatal lamb model of induced surfactant deficiency. Eight lambs were anesthetized and ventilated in supine position. Surfactant deficit was induced by saline lung lavage. After deflation, lungs were filled with 25ml/kg perflubron over 18s, and TLV was initiated. Electrical impedance tomography data was recorded from electrodes placed around the chest, during the first 10min and at 120min of TLV. Lung perfusion was also assessed using hypertonic saline injection during apnea. In addition, fluoroscopic sequences were recorded during initial lung filling with perfluorocarbons, then at 10 and 60min of TLV. Twelve lambs were used as controls for histological comparisons. Transition to TLV involved a short period of increased total lung volume (p=0.01) secondary to recruitment of the dependent lung regions. Histological analysis shows that TLV was protective of these same regions when compared to gas-ventilated lambs (p=0.03). The non-dependent lung regions filled with perflubron over at least 10 minutes, without showing signs of overdistention. Tidal volume distribution was more homogenous in TLV than during the preceding gas ventilation. Perflubron filling was associated with a non-significant increase in the anterior distribution of the blood perfusion signal, from 46 ± 17% to 53 ± 6% (p = 0.4). However, combined to the effects on ventilation, TLV had an instantaneous effect on ventilation-perfusion relationship (p=0.03), suggesting better coupling. Conclusion: transition to TLV requires at least 10 minutes, and involves air evacuation or dissolution in perflubron, dependent lung recruitment and rapid ventilation-perfusion coupling modifications. During that time interval, the total lung volume transiently increases. Considering the potential deleterious effect of high lung volumes, one must manage this transition phase with care and, we suggest using a real-time monitoring system such as electrical impedance tomography.